Improving the intrinsic spatial resolution performance of the continuous miniature crystal element (cMiCE) detector - Ling, Tao (2007)
We have previously reported performance characteristics of a cMiCE detector composed of a 50 mm by 50 mm by 8 mm thick slab of LYSO, coupled to a 64 channel flat-panel PMT. In that work, all 64 PMT channels were digitized and a statistics-based positioning method was used for event positioning. In characterizing the detector, the intrinsic spatial resolution performance for the corner sections of the crystal was degraded compared to the central section of the crystal, even when using our SBP method. It is our belief that the poorer positioning performance at the corners is because much of the light is lost (i.e., not collected by our PMT). To offset this problem, we propose to place light sensors (i.e., micro-pixel avalanche photo diodes, MAPD) at the corners along the short edge of the crystal. The new design would require an additional 8 MAPD devices. Monte Carlo simulation was used to compare the performance of the original cMiCE design and this new enhanced design. Simulation results using DETECT2000 are presented. In addition to doing light ray tracing, GEANT was used to track gamma interactions (i.e., Compton scatter and photoelectric absorption) in the crystal. Thus the simulations include the effects of Compton scatter in the detector. Results indicate that adding the sensors improves the intrinsic spatial resolution performance from 0.99 mm FWHM to 0.79 mm FWHM for the corner section of the crystal, thereby nearly matching the intrinsic spatial resolution of the center section of the crystal (i.e., 0.73 mm FWHM). These results are based upon using dual-DOI look up tables. Additional results were that energy histograms were better using just the 64 channels from the flat panel PMT than using all 72 signal channels.